Research trends and hotspots of central sleep apnea: a bibliometric analysis - Hao, Yin-Chao; Zhu, Meng-Chu; Li, Wei-Xuan; Sha, Jing-Jing; Dong, Xue-Tong; Wang, Song-Jun; Lu, Chao-Long (Frontiers in Neurology, 2025)
Central sleep apnea (CSA), characterized by unstable ventilatory control during sleep, poses significant health risks, particularly in patients with cardiovascular comorbidities. This bibliometric analysis evaluated 1,687 CSA-related publications (2004–2025) from the Web of Science Core Collection. Annual publications surged post-2016, peaking in 2021 (115 articles), reflecting growing research interest. The U.S. and Germany dominated contributions, with American Journal of Respiratory and Critical Care Medicine as the top journal. Keyword analysis revealed three focal areas: CSA-heart failure interactions (e.g., mortality, ejection fraction), CSA mechanisms (e.g., hypercapnia, chemosensitivity), and clinical management (e.g., adaptive servo-ventilation, phrenic nerve stimulation). Emerging trends include pediatric CSA, pathophysiology, and AI-driven diagnostics. International collaboration and multidisciplinary approaches are critical for advancing CSA research. Limitations include database constraints and evolving literature. This study maps CSA research trends, highlights gaps, and guides future investigations into mechanisms, biomarkers, and personalized therapies.